Preparation method and application of titanium dioxide / high-entropy alloy micro-nano structure battery photo-thermal positive electrode
By using the preparation method of the photothermal positive electrode of the titanium dioxide/high entropy alloy micro-nano structure battery in solar photothermal lithium batteries, the energy loss problem caused by different solar light incident angles in the prior art is solved, and efficient light absorption and all-round photothermal conversion are achieved, and the energy density and cycle stability of the battery are improved.
Patent Information
- Application Number
- CN202411925001.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
In practical application, the existing solar photothermal conversion structures are energy loss due to sunlight irradiation from different angles, making it difficult to achieve all-round and efficient photothermal conversion.
The photothermal positive electrode of the titanium dioxide/high entropy alloy micro-nano structure battery is prepared by preparing the seed layer on the substrate, adjusting the hydrothermal growth temperature and annealing temperature, and preparing a high-entropy alloy on its surface to form a photothermal conversion film with a titanium dioxide/high entropy alloy micro-nano structure.
It realizes efficient light absorption and all-round photothermal conversion within the full spectrum range, improves the energy density and cycle stability of solar photothermal lithium batteries, and broadens its working temperature zone.
Smart Images

Figure CN119742382A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar thermal conversion and photocatalysis technology, and in particular to a preparation method and application of a titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode. Background Art
[0002] With the continuous growth of global energy demand and the increasing attention paid to environmental protection, renewable energy, as a green and sustainable energy option, has gradually become an important direction for future energy development. Traditional fossil energy, especially oil, coal and natural gas, not only faces the dilemma of resource depletion, but also releases a large amount of greenhouse gases during mining, transportation and use, leading to global climate change and air pollution. In contrast, renewable energy is continuous, inexhaustible, and has significant environmental advantages. It is the key to achieving carbon neutrality goals and reducing damage to the ecological environment.
[0003] At present, renewable energy sources such as solar energy, wind energy, biomass energy and geothermal energy have been widely studied and applied. As one of the most abundant renewable energy sources, solar energy not only has huge resource potential, but also can be directly converted into electrical energy or thermal energy, and has a wide range of applications.
[0004] However, although the technological progress of renewable energy has greatly improved its economy and applicability, it still faces many challenges in practical application. The intermittent and fluctuating characteristics of solar and wind energy limit their stable supply capacity; and the existing energy storage technology and grid infrastructure have not yet fully met the needs of large-scale renewable energy access and efficient transmission. Therefore, how to improve the utilization efficiency of renewable energy, especially in the process of energy storage and conversion, has become an important issue that needs to be solved urgently.
[0005] The excellent solar thermal conversion performance of the highly efficient solar light-heat conversion structures reported so far mostly depends on vertical incident light conditions. 2 Solar energy is a key challenge for solar thermal absorbers, such as solar cells, desalination, etc. Sunlight hits the absorber surface from different angles, which inevitably leads to significant energy loss. Therefore, how to achieve all-round and efficient photothermal conversion so that the absorber can maintain high conversion efficiency at different incident angles has become a major challenge for solar thermal absorbers. Summary of the invention
[0006] Based on the problem that the current solar light-heat conversion structure will inevitably lead to significant energy loss in practical applications, the purpose of the present invention is to provide a method for preparing a titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode. The photothermal conversion film has the characteristics of environmental protection, health, pollution-free and structural stability, can be used for a long time in practical applications, and also has the characteristics of efficient light absorption, photothermal conversion and photocatalysis, which is suitable for Li-CO 2 The field of batteries.
[0007] The present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present application provides a method for preparing a titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode, comprising the following steps:
[0009] preparing a seed layer on a substrate;
[0010] Titanium dioxide nanowire array structures with different morphologies were prepared by adjusting the hydrothermal growth temperature and the annealing temperature after hydrothermal growth.
[0011] A high entropy alloy is prepared on the surface of the titanium dioxide nanowire array structure to form a titanium dioxide / high entropy alloy micro-nanostructured photothermal conversion film.
[0012] This photothermal conversion film can realize the synergistic conversion of light, heat and photoelectricity, is suitable for a variety of high-efficiency energy conversion applications, and can be used as the positive electrode material of solar thermal lithium batteries to achieve efficient electrical energy conversion and storage.
[0013] The photothermal conversion film combines the photothermal effect of metal plasma and the light trapping effect of semiconductor three-dimensional nanostructures, and can achieve efficient light absorption and all-round photothermal conversion in the full spectrum. In the solar thermal lithium battery system, the photothermal conversion film is used as a positive electrode material to improve the energy density and cycle stability of the battery and broaden its operating temperature range. This material is not only suitable for Li-CO 2 Batteries can also play an important role in the field of carbon dioxide reduction and have broad application prospects.
[0014] Furthermore, the substrate is made of hydrophilic material, including hydrophilic carbon cloth.
[0015] Furthermore, before preparing the seed layer on the substrate, the substrate is pretreated, specifically: the substrate is ultrasonically cleaned multiple times using acetone, ethanol and deionized water respectively. Ultrasonic cleaning is used to remove grease and excess organic impurities on the surface, thereby obtaining a clean surface, providing a better experimental basis for the subsequent orderly growth of nanowires.
[0016] Furthermore, the method for preparing a seed layer on a substrate comprises the following steps:
[0017] Preparation of seed layer precursor solution: dissolving a titanium source in an organic solvent and stirring until the mixed solution has no yellow precipitate or floccules and is transparent and colorless, then stopping stirring to form a seed layer precursor solution;
[0018] Forming a seed layer on the substrate: Place the cleaned substrate into the seed precursor solution, soak for 30 minutes, form a seed layer on the surface of the substrate by a constant temperature and uniform speed pulling method, then place it in an oven, shape and dry it under constant temperature conditions, and finally calcine the dried product at high temperature to obtain a substrate containing a seed layer.
[0019] Furthermore, a hydrothermal method is used to prepare titanium dioxide nanowire array structures with different morphologies, comprising the following steps:
[0020] Preparation of hydrothermal precursor solution: Mix the titanium source with the hydrochloric acid solution, and then stir at room temperature until there is no white flocculent on the surface of the solution or the titanium foil is completely dissolved, and the solution is transparent and colorless and can be used;
[0021] Preparation of TiO 2 Nanowire array: The prepared substrate containing the seed layer and the precursor solution are transferred to a reaction vessel for reaction. After the reaction is completed, the product is taken out for rinsing and drying, and finally annealed at high temperature to obtain TiO 2 Nanowire arrays.
[0022] Furthermore, the titanium source includes tetrabutyl titanate or titanium foil.
[0023] Furthermore, the method for preparing a high entropy alloy on the surface of a titanium dioxide nanowire array structure comprises the following steps:
[0024] Select a metal salt precursor and dissolve it in the solution, ensuring that the metal salt is evenly mixed;
[0025] The mixed solution is coated on a substrate, which is then placed in an argon glove box and subjected to an electric pulse to rapidly heat the substrate, with the thermal shock time controlled within a few milliseconds.
[0026] The particle structure is quickly locked through high-speed cooling to avoid phase separation, and ultimately form high-entropy alloy nanoparticles of a single-phase solid solution.
[0027] Furthermore, the metal salt precursor includes AuCl 4 H 3 O and Cl 3 H 2 ORu.
[0028] In a second aspect, the present application provides a titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode, which is prepared using the above-mentioned preparation method.
[0029] In a third aspect, the present application provides a Li-CO 2 A battery, comprising the above-mentioned titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode.
[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0031] (1) The three-layer structure of the photothermal conversion film in the present invention has the characteristics of environmental protection, health, pollution-free and structural stability, and can be used for a long time in practical applications. In addition, the solar light absorption film prepared by combining the constant temperature pulling method, hydrothermal method and thermal shock wave technology has the characteristics of high efficiency light absorption, photothermal conversion and photocatalysis, and is suitable for Li-CO 2 The field of batteries.
[0032] (2) The present invention prepares the seed layer by a constant temperature pulling method, and deposits a dense and uniform seed layer on the surface of the substrate by precisely controlling the temperature and lifting speed, providing good basic conditions for the subsequent growth of the titanium dioxide nanowire array structure; the diameter and length of the titanium dioxide nanowire array structure can be micro-regulated by the growth parameters of the hydrothermal method (such as: calcination temperature and time, hydrothermal method holding temperature and annealing temperature after hydrothermal growth), thereby achieving precise control of the size of the nanowires. In addition, a high entropy alloy is further prepared on the surface of the titanium dioxide nanowire array structure by a thermal shock wave technology method, thereby achieving the precise preparation of a carbon dioxide / high entropy alloy composite structure with excellent light absorption and photothermal properties.
[0033] (3) The titanium dioxide-high entropy alloy photothermal conversion film in the present invention combines the metal plasma photothermal effect and the light trapping effect of the semiconductor nanostructure, and can achieve efficient light absorption and all-round photothermal conversion in the full spectrum. In the photothermal lithium battery system, the titanium dioxide-high entropy alloy photothermal conversion film structure is used as a positive electrode material. Due to its excellent light collection ability, photoelectric and photothermal effects, and high electron-hole separation efficiency, it helps to improve the energy density and cycle stability of the battery and expand its operating temperature range. Therefore, this structure has broad application prospects in the field of solar thermal lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0035] Figure 1The TiO prepared by changing the hydrothermal temperature in the embodiment of the present invention 2 Scanning electron microscopy image of the NWs array structure;
[0036] Figure 2 In the embodiment of the present invention, the thermal shock wave technology is used to 2 SEM image of Au and Ru high entropy alloys prepared on NWs array structure;
[0037] Figure 3 The TiO prepared in the embodiment of the present invention 2 XRD patterns of NWs and TiO 2 @XRD patterns of Au / Ru composite structures; (a) is TiO prepared under hydrothermal conditions of 140°C and 160°C 2 XRD pattern of NWs, the diffraction peaks of which correspond to those of anatase; (b) is the diffraction peaks of TiO 2 @XRD pattern of Au / Ru composite structure, the diffraction peak corresponds to Ti 5 O 9 Standard cards of
[0038] Figure 4 The TiO prepared in the embodiment of the present invention 2 @Au / Ru composite structure and XRD patterns of TiO 2 @XRD pattern of Au / Ru composite structure, where (a) is TiO 2 @XRD pattern of Au / Ru composite structure, the diffraction peak corresponds to Au 2 O 3 (b) is the standard card of TiO 2 @XRD pattern of Au / Ru composite structure, its diffraction peak corresponds to the standard card of RuTi;
[0039] Figure 5 The TiO prepared in the embodiment of the present invention 2 Absorption spectra of NWs and TiO 2 @Au / Ru composite structure film absorption spectrum, where (a) is TiO 2 Absorption spectrum of NWs; (b) TiO 2 @Au / Ru composite structure film absorption spectrum;
[0040] Figure 6 The TiO prepared in the embodiment of the present invention 2 @Surface temperature distribution of Au / Ru composite structure film under strong sunlight irradiation;
[0041] Figure 7 The solid Li-CO 2The battery capacity is limited to 500mAhg at 150℃ -1 , current density is 500mAg -1 The electrochemical performance of . DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0043] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, well-known materials or methods are not specifically described.
[0044] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" that appear in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any appropriate combination and / or sub-combination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items. In addition, those skilled in the art will be able to combine and combine different embodiments or examples described in this specification and features of different embodiments or examples, without contradicting each other.
[0045] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0046] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0047] Example
[0048] This embodiment provides a method for preparing a titanium dioxide / high entropy alloy (Au / Ru) micro-nanostructure battery photothermal positive electrode, which is carried out according to the following steps:
[0049] S1. Use acetone, ethanol and deionized water to perform ultrasonic cleaning on the carbon cloth substrate multiple times to remove grease and excess organic impurities on its surface, thereby obtaining a clean surface and providing a better experimental basis for the subsequent orderly growth of nanowires.
[0050] S2. preparing a seed layer on a clean carbon cloth substrate.
[0051] S2-1. Prepare a seed layer precursor solution: dissolve 660 μL of tetrabutyl titanate as a titanium source in 25 ml of isopropanol solvent and stir until the mixed solution has no yellow precipitate or floccules and is transparent and colorless, then stop stirring to form a seed layer precursor solution;
[0052] S2-2. Forming a seed layer on the substrate: Place the cleaned substrate into the seed precursor solution and soak for 30 minutes to form a seed layer on the surface of the substrate. Then place it in an oven and dry it at a constant temperature. Finally, calcine the dried product at 550°C to obtain a carbon cloth substrate containing a seed layer.
[0053] S3. Titanium dioxide nanowire array structures with different morphologies were prepared by adjusting the hydrothermal growth temperature (140°C, 160°C) and the annealing temperature after hydrothermal growth (550°C, 500°C).
[0054] S3-1. Prepare the hydrothermal precursor solution: First, use 660 μL of tetrabutyl titanate as the titanium source; second, mix 12 mol / L concentrated hydrochloric acid (HCl) and deionized water (DI) in a certain proportion to make 30 mL of 6 mol / L hydrochloric acid, and stir evenly; finally, add the prepared titanium source to the prepared hydrochloric acid solution, stir for several hours at room temperature, until no white flocs appear on the surface of the solution, or the titanium foil is completely dissolved, and the solution becomes transparent and colorless, then the precursor solution is obtained.
[0055] S3-2. Preparation of TiO 2 NWs array: The prepared seed layer carbon cloth and precursor solution were transferred to the reactor. After reacting at 140°C for 15 hours, the sample was taken out for rinsing and drying. Then the sample was annealed at high temperature for 2 hours to finally obtain TiO 2 NWs array.
[0056] S4. Prepare a high entropy alloy on the surface of the titanium dioxide nanowire array structure to form a titanium dioxide / high entropy alloy micro-nanostructure photothermal conversion film.
[0057] S4-1. Select metal salt precursor (AuCl 4 H 3 O and Cl 3 H 2 ORu) and dissolved it in the solution to a concentration of 0.1 μmol / cm 2 , ensuring that the metal salts are evenly mixed.
[0058] S4-2, apply the mixed solution to the TiO 2 NWs structure on carbon cloth.
[0059] S4-3. Place the sample in an argon glove box to avoid oxygen interference, and apply electric pulses to rapidly heat the substrate, with the thermal shock time controlled at 50 milliseconds. During the thermal shock process, the high temperature causes the metal salt precursor to decompose into liquid metal, and fission and polymerization occur between the liquid metals.
[0060] S4-4, by rapidly cooling the particles to quickly lock the particle structure and avoid phase separation, finally forming single-phase solid solution high entropy alloy nanoparticles (HEA-NPs) to obtain TiO 2 @Au / Ru composite structure light absorption film.
[0061] The TiO prepared according to the above specific implementation steps 2 The SEM images of NWs arrays are shown in Figure 1 As shown in Figure 2, it can be observed that the nanowire array is regular and orderly. 2 Au and Ru high entropy alloys were prepared on the surface of NWs, and their SEM images are shown in Figure 2 As shown in the figure, TiO 2 There are 50-100 nm nanoparticles evenly distributed near the NWs, which are Au and Ru high-entropy alloy nanoparticles.
[0062] like Figure 3 (a) shows that in order to verify the 2 We investigated the structures of TiO NWs prepared at 140 °C and 160 °C under hydrothermal conditions. 2 The NWs photothermal conversion film was tested by XRD, and the results showed that its diffraction peaks were basically consistent with the standard diffraction peaks of anatase titanium dioxide. Subsequently, we prepared a high entropy alloy on its surface and performed an XRD test, and found that the diffraction peaks became more chaotic, which was consistent with the standard diffraction peaks of TiO2. 5 O 9 After comparing with the standard card, it is found that the diffraction peaks are basically consistent, such as Figure 3 (b). Figure 4 As shown in (a), Au 2 O 3 The standard card is compared with its diffraction peak, and the results are basically consistent; Figure 4 As shown in (b), the RuTi standard card is compared with its diffraction peak, and the results are basically consistent. This shows that the four elements of Ti, O, Au, and Ru do exist in the sample.
[0063] The TiO prepared according to the above specific implementation steps 2 NWs array structure and prepared TiO 2 @The light absorption curve of Au / Ru composite structure is as follows Figure 5As shown. In the wide spectral range of 200nm to 2500nm, the light absorption rate of the film is stable at about 87% and 91%. 2 @Au / Ru composite structure was subjected to photothermal test. Under simulated sunlight, its surface temperature reached 74.2℃. Figure 6 As shown. TiO prepared based on the above specific implementation steps 2 @Au / Ru composite structure, we used it as the positive electrode, LAGP as the solid electrolyte, and Li sheet as the negative electrode. We conducted charge and discharge tests under light conditions. The results showed that the structure can be effectively cycled for 45 hours. Figure 7 As shown. The LAGP solid electrolyte is composed of lithium, aluminum, germanium and phosphorus elements, has high ion conductivity and good stability, and is suitable for use at high temperatures and high voltages. The advantage of LAGP electrolyte lies in its high lithium ion conductivity. Compared with traditional liquid electrolytes, LAGP has higher safety and avoids problems such as leakage or fire that may be caused by liquid electrolytes.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that it is still possible to modify the technical solutions described in the aforementioned embodiments, or to replace some or all of the technical features therein by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode, characterized in that: The following steps are involved: preparing a seed layer on a substrate; Titanium dioxide nanowire array structures with different morphologies were prepared by adjusting the hydrothermal growth temperature and the annealing temperature after hydrothermal growth. A high entropy alloy is prepared on the surface of the titanium dioxide nanowire array structure to form a titanium dioxide / high entropy alloy micro-nanostructured photothermal conversion film.
2. The method for preparing the titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode according to claim 1, characterized in that: The substrate is made of hydrophilic material.
3. The method for preparing the titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode according to claim 1, characterized in that: Before preparing the seed layer on the substrate, the substrate is pretreated, specifically: the substrate is ultrasonically cleaned multiple times using acetone, ethanol and deionized water respectively.
4. The method for preparing a titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode according to claim 1, characterized in that: The method for preparing a seed layer on a substrate comprises the following steps: Preparation of seed layer precursor solution: dissolving a titanium source in an organic solvent and stirring until the mixed solution has no yellow precipitate or floccules and is transparent and colorless, then stopping stirring to form a seed layer precursor solution; Forming a seed layer on the substrate: After the cleaned substrate is immersed in a seed precursor solution, a seed layer is formed on the surface of the substrate, and then it is placed in an oven and dried under constant temperature conditions. Finally, the dried product is calcined at a high temperature to obtain a substrate containing a seed layer.
5. The method for preparing the titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode according to claim 1, characterized in that: Titanium dioxide nanowire array structures with different morphologies are prepared by a hydrothermal method, comprising the following steps: Preparation of hydrothermal precursor solution: Mix the titanium source with the hydrochloric acid solution, and then stir at room temperature until there is no white flocculent on the surface of the solution or the titanium foil is completely dissolved, and the solution is transparent and colorless and can be used; Preparation of TiO2 nanowire array: The prepared substrate containing the seed layer and the precursor solution are transferred to a reaction container for reaction. After the reaction is completed, the product is taken out for rinsing and drying, and finally high-temperature annealing is performed to obtain the TiO2 nanowire array.
6. The method for preparing the titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode according to claim 5, characterized in that: The titanium source includes tetrabutyl titanate or titanium foil.
7. The method for preparing a titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode according to claim 1, characterized in that: The method for preparing a high entropy alloy on the surface of a titanium dioxide nanowire array structure comprises the following steps: Select a metal salt precursor and dissolve it in the solution, ensuring that the metal salt is evenly mixed; The mixed solution is coated on a substrate, which is then placed in an argon glove box and subjected to an electric pulse to rapidly heat the substrate, with the thermal shock time controlled within a few milliseconds. The particle structure is quickly locked through high-speed cooling to avoid phase separation, and ultimately form high-entropy alloy nanoparticles of a single-phase solid solution.
8. The method for preparing the titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode according to claim 7, characterized in that: The metal salt precursor includes AuCl4H3O and Cl3H2ORu.
9. A titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. A Li-CO2 battery, characterized in that: It includes the titanium dioxide / high entropy alloy micro-nanostructure battery photothermal positive electrode as described in claim 9.
Citation Information
Patent Citations
A binder-free conductive agent-free lithium carbon dioxide battery electrode sheet and preparation method thereof
CN109167018A
Novel lithium-carbon dioxide battery and preparation of positive electrode material thereof
CN110492203A
Design and optimization method of lithium ion battery, electrodes and material thereof
CN111081979A
Preparation method of multifunctional photothermal conversion film with semiconductor-metal nanowire structure
CN116143217A
Method for preparing high-entropy alloy nano-catalyst through high-temperature liquid phase impact
CN117020217A